2004
DOI: 10.1081/prg-120028292
|View full text |Cite
|
Sign up to set email alerts
|

Markers for Presymptomatic Prediction of Preeclampsia and Intrauterine Growth Restriction

Abstract: Preeclampsia and intrauterine growth restriction are both characterized by placental malfunction. The pathological processes of abnormal trophoblast invasion, partial absence of maternal spiral artery modification, increased apoptosis of trophoblast cells, and placental ischemia are all associated with the release of specific molecules. These proteins, as well as cell-free fetal DNA and RNA might be detected in the maternal peripheral circulation, quantified, and used for early identification and prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 100 publications
1
40
0
1
Order By: Relevance
“…The authors concluded that total fibronectin might be useful to determine relative risks, but is a poor predictor in a low risk population. Tjoa et al repeated this plasma analysis of total fibronectin in a similar low risk population, with emphasis on the first trimester and found no differences in plasma total fibronectin levels in pregnant women between 7th-20th gw [1]. Ostlund et al showed relation of plasma total fibronectin to blood pressure in women who developed preeclampsia in 16 gw and even higher in those with laboratory signs of organ involvement [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that total fibronectin might be useful to determine relative risks, but is a poor predictor in a low risk population. Tjoa et al repeated this plasma analysis of total fibronectin in a similar low risk population, with emphasis on the first trimester and found no differences in plasma total fibronectin levels in pregnant women between 7th-20th gw [1]. Ostlund et al showed relation of plasma total fibronectin to blood pressure in women who developed preeclampsia in 16 gw and even higher in those with laboratory signs of organ involvement [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by maternal hypertension, proteinuria, edema, potentially causing fetal growth restriction and premature delivery [1]. This common pregnancy-associated disease is a leading cause of perinatal morbidity and mortality of mother and child [2].…”
Section: Introductionmentioning
confidence: 99%
“…In preeclampsia and idiopathic small for gestational age (SGA) pregnancies, cytotrophoblast invasion is restricted with a limited remodelling of spiral arteries, thus resulting in reduced uteroplacental perfusion (Lim et al 1997). Small fetuses due of intrauterine growth restriction (IUGR) are at higher risk for poor perinatal and long-term outcome (Baschat 2004;Tjoa et al 2004), being associated with an increased risk of heart diseases and type 2 diabetes mellitus (Barker 1998). The most common definition of IUGR is a birth weight lower than the 10th percentile when adjusted to gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a reliable biomarker has yet to be identified. [5][6][7][8] A novel biomarker of vascular epithelium disorders is lipocalintype prostaglandin D synthase (L-PGDS). Accordingly we measured urine and blood L-PGDS concentrations in preeclamptic patients and normal pregnancy women and determined whether L-PGDS is a potential biomarker of preeclampsia or not.…”
Section: Introductionmentioning
confidence: 99%